ESTUDO COMPARATIVO DA COMPOSIÇÃO CORPORAL ENTRE IDADES DE CRIANÇAS PRÉ-PUBERES DO SEXO FEMININO - Alessandra Regina dos Santos; Emerson José Zechin; Tadeu Paccagnella; Kleber Parada; Milton Faria Junior (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
The aim of the study was to determine the differences in body composition of female children between seven and eleven years old. The sample consisted of 211 children, selected randomly, from town schools from the countryside of Sao Paulo. The children underwent to total body weight, height and triceps skinfold thickness (TSF) and subscapular (DCS) assessment. The values obtained were used to calculate the percentage of Body Fat (% BF), fat mass weight (PMG) and Lean Mass Weight (PMM). The data were submitted to ANOVA for all variables, and subsequently for multiple comparison of variables between ages, was used Dunn's Method with a significance level of p <0.05. Significant differences were observed between the ages in relation a percentage of body fat, fat mass and lean mass weight. It was concluded that children aged seven to eleven years tend to increase their body weight with increasing age, due to the lean and fat mass increasing weight.